The Main Features of Hydraulic Fill Soils and River Dnieper Alluvial Deposits in the Kyiv Region - Rashchenko, Andriy; Dyptan, Tatyana; Malyshev, Oleg (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The features of the tectonic structure together with the geological and geomorphological zoning of Kyiv city are highlighted in the article. Particular attention is paid to the floodplains of the Dnieper River, which were formed by the hydraulic fill method. As a rule, such sites were created for new constructions and were quickly built up with low rise buildings, the bases of which were made using such hydraulic soils.
Keywords: alluvial deposits; floodplains; sandy soils; tectonic structure; deformations; Kyiv Region; osady aluwialne; równina zalewowa; gleby piaszczyste; budowa tektoniczna; deformacje; Kijów (region)